ChemInform Abstract: A Mild Multistep Conversion of N‐Protected α‐Amino Acids into N‐Protected β3‐Amino Acids Utilizing the Nef Reaction. Issue 30 (4th July 2013) - Sleebs, Brad E.; Nguyen, Nghi H.; Hughes, Andrew B.
Abstract α‐Amino acids (I) and (VII) are converted into chiral γ‐amino nitroalkanes of type (V) in a three‐step sequence.